2015
DOI: 10.1515/bsrj-2015-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Great Recession on Monetary and Fiscal Policy in Developed Market Economies

Abstract: Background: With the occurrence of the crisis in 2007, which caused the largest economic contraction since the Great Depression in the thirties, it has become evident that the previous understanding of strategies, effects and roles of monetary and fiscal policy should be redefined. Objectives: The aim of this paper is to illustrate a possible expected change in monetary and fiscal policy in developed market economies that could occur as a consequence of the Great Recession. Methods/Approach: The paper provides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Feraru concluded that a justification for the pro-cyclicality observed is that tax authorities can engage in promoting an anti-cyclical tax policy, but they do not have adequate information on current cyclical conditions, real-time indicators associated with the economic cycle are subject mainly due to the significant uncertainty of estimates of potential GDP revisions [16]. D. Šehović analyzed the impact of the large recession on fiscal and monetary policy in developed market economies [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Feraru concluded that a justification for the pro-cyclicality observed is that tax authorities can engage in promoting an anti-cyclical tax policy, but they do not have adequate information on current cyclical conditions, real-time indicators associated with the economic cycle are subject mainly due to the significant uncertainty of estimates of potential GDP revisions [16]. D. Šehović analyzed the impact of the large recession on fiscal and monetary policy in developed market economies [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, recently developed countries have guaranteed the independence of the Central Bank in order to prevent inflation risks arising from the arbitrary use of monetary policy. Thus, the importance of monetary policy and inflationary taxation on fiscal soundness has weakened [26]. Especially in the case of European Union countries, it is argued that monetary policy cannot be utilized in accordance with the reality of each country, and thus, it is further argued that there is a limit to the guarantee of financial stability [13,26].…”
Section: Economic Factorsmentioning
confidence: 99%
“…As confidence in monetary policy weakened following, the influence of fiscal policy began to be emphasized [26]. The most important variable is the aging population.…”
Section: Economic Factorsmentioning
confidence: 99%